RANCANG BANGUN SISTEM PEMBERIAN PAKAN AYAM BROILER BERBASIS MIKROKONTROLLER - Farichah, Ainul; Riadi, Aditya Akbar; Murti, Alif Catur (Jurusan Teknologi Informasi Universitas Semarang, 2021)
Broiler Chicken Feed System is a tool that is implemented using microcontroller technology. The focus of technology in industry 4.0 is that all devices can be controlled and monitored remotely, as long as they are connected to a network. In accordance with this vision, this technology makes it easier for farmers to feed chickens that were originally still using manual labor, then made automatically by implementing microcontroller technology consisting of SIM800L, Arduino, servo motors, and ultrasonic sensors. By using two ultrasonic sensors that are placed to enter orders and provide information about the stock of chicken feed this technology can work well. The focus of this technology is that it can be used for remote monitoring. Not only that, this technology can also send notifications to the farmer's smartphone to show the condition of the chicken feed stock that is still available. By applying this technology, chicken farmers can combine and feed their chickens from anywhere.